The crystal structure of nitroxyl-κN-{hydridotris(3-trifluoromethyl-5-methylpyrazolyl-1-yl-κN3)borato}nickel(II), C15H13BF9N7NiO - Fujisawa, Kiyoshi; Kataoka, Taisei; Terashima, Kohei; Tiekink, Edward R. T. * (De Gruyter, 2022)
15H13BF9N7NiO, orthorhombic, Pnma (no. 62), a = 17.8513(3) Å, b = 13.3869(2) Å, c = 8.5944(2) Å, V = 2053.83(7) Å3, Z = 4, Rgt (F) = 0.0235, wRref (F 2) = 0.0690, T = 124(2) K.